Pengembangan Buku Panduan Pendidikan Karakter Optimis Berbasis Permainan Tradisional Untuk Anak Usia 10-12 Tahun - K. Indah Dwi Prastiwi; Gregorius Ari Nugrahanta (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2023)
The children’s capitulate behavior, the lack of self-recognition, and the lack of motivation reflect a low optimistic character. This research aims to develop a character education handbook for 10-12 years old children. The method used was Research and Development (R&D) type ADDIE involving ten elementary school teachers for the needs analysis. There were ten validators consisting of five elementary school teachers, four expert lecturers, and one cultural practitioner who acted as expert judges. Eight children participated in the character education handbook limited trial. The results of this study showed that 1) The traditional game basis of an f optimistic character education handbook for 10-12 years old children was developed through the analysis, design, development, implementation, and evaluation stages; 2) the character education handbook had an